Supply chain effects of China’s fast growing marine economy on greenhouse gas emissions - Man Li; Kuishuang Feng; Heran Zheng; Chen Pan; Jing Meng; Jiashuo Li; Dabo Guan; Yuan Li (Environmental Research Letters, 2021)
The marine economic activities has become a vital economic driving force for development of China’s economy. However, the trajectory of greenhouse gas (i.e. GHG) emissions associated the fast growing marine economy and its role in emission mitigation remain unclear. Through compiling high-resolution and time-series environmental input–output tables for 2002, 2007, 2012 and 2017, this study quantify development of 13 key marine industries in driving national economic development and its supply chains, and assesses the direct and indirect contributions of marine industries to the national economy and GHGs emissions. Our results show that the total emissions of marine economy increased by 2.3 times from 2002 to 2017, and the share of that in national total emissions increased by 43.3%. The economic output of marine economy may lead to up to 1.8 times of the total economic output in the upstream industries, while the indirect emissions of major marine economy embodied in the upstream supply chains is on average 3.5 times of direct emissions from marine industries. Our findings highlight the necessity of considering total supply chain GHGs emissions associated with the fast growing marine economy to better achieve China’s climate mitigation targets.